"God's Operating Manual": Marriage Theologies in Ultra-Orthodox and Evangelical Marital Guidebooks. (April 2020) - Novis-Deutsch, Nurit
Evangelical Protestant and Jewish ultra-Orthodox communities are two high-tension religious groups that share an emphasis on traditional family values. Their leaders must communicate the virtues of religious marriage to "curious outsiders" while supporting "distressed insiders" whose marriages have become unstable. This article analyzes thirty marital guidebooks, fifteen ultra-Orthodox, and fifteen evangelical Protestant to probe their strategies. A key finding is the abundance of marriage theologies in the guidebooks, that is, schemas that endeavor to make sense of marriage and its vicissitudes by explicating God's role and expectations for the couple. Five shared and four denomination-specific marriage theologies are identified and discussed.